Pengaruh Kualitas Layanan Terhadap Kepuasan Nasabah Dalam Bertransaksi Dibank Syariah (Btn Syariah) Diuniversitas Muhammadiyah Makassar - Cecet Eriani; Buyung Romadhoni; Firman Syah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is a type of quantitative research with the aim of determining the Effect of Service Quality on Customer Satisfaction in Transactions at the Sharia Bank (BTN Syariah) of the Muhammadiyah University of Makassar. This sample was taken from the BTN Syariah Bank branch in Makassar City with a population of 5400 customers from September to the end of November 2024 and a sample of 98 customers. Based on the results of data research using statistical calculations regarding the effect of service quality on customer satisfaction in transactions at the Sharia Bank (BTN Syariah) of the Muhammadiyah University of Makassar, the author concludes that Service Quality has a positive and significant effect on customer satisfaction. Good service quality will increase customer satisfaction in transactions at the BTN Syariah Sharia Bank because it can be seen from the calculation results, namely a coefficient value of 0.638 and a significant value of less than 0.05, which is 0.001